Penanaman Nilai-Nilai Religius dalam Membentuk Akhlakul Karimah Siswa Kelas X SMA Negeri 1 Sukodadi - M. Tubagus Imam Yazid Busthomi; Khotimah Suryani (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
Religious values are an aspect of human personality that cannot stand alone; they are related to other aspects of personality and must be instilled in children as early as possible so as not to hinder their future tasks and development. Religious abilities do not develop on their own; they are acquired through willpower and encouragement from others, including teachers and parents, who must set a good example and be role models. This study aims to describe the process of instilling religious values in shaping the good character of students at Sukodadi 1 State Senior High School. The background of this study is based on the phenomenon of moral decline among teenagers due to the influence of globalisation, as well as the importance of character education based on religious values. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of this study show that the activities carried out in instilling religious values include starting with the habit of smiling, greeting, and saying hello, the habit of Friday morning studies, the habit of praying together before starting lessons, the habit of being honest, the habit of being responsible, the habit of being disciplined, and the habit of praying. The supporting factors in the implementation of religious values include: the support and attention of parents and